Engineering the Photocatalytic Behaviors of g/C3N4‐Based Metal‐Free Materials for Degradation of a Representative Antibiotic. (18th June 2020) - Deng, Yanchun; Liu, Jun; Huang, Yanbin; Ma, Mengmeng; Liu, Kong; Dou, Xiaomin; Wang, Zhijie; Qu, Shengchun; Wang, Zhanguo
Abstract: Graphitic carbon nitride (g/C3 N4 ) is of promise as a highly efficient metal‐free photocatalyst, yet engineering the photocatalytic behaviours for efficiently and selectively degrading complicated molecules is still challenging. Herein, the photocatalytic behaviors of g/C3 N4 are modified by tuning the energy band, optimizing the charge extraction, and decorating the cocatalyst. The combination shows a synergistic effect for boosting the photocatalytic degradation of a representative antibiotic, lincomycin, both in the degradation rate and the degree of decomposition. In comparison with the intrinsic g/C3 N4, the structurally optimized photocatalyst shows a tenfold enhancement in degradation rate. Interestingly, various methods and experiments demonstrate the specific catalytic mechanisms for the multiple systems of g/C3 N4 ‐based photocatalysts. In the degradation, the active species, including ·O2 −, ·OH, and h +, have different contributions in the different photocatalysts. The intermediate, H2 O2, plays an important role in the photocatalytic process, and the detailed functions and originations are clarified for the first time. Abstract : The photocatalytic behaviors of g/C3 N4 are modified via multiple strategies. The combination of CD‐rGO‐O‐g/C3 N4 shows superior activity compared to pristine g/C3 N4 and a synergistic effect for photocatalytic degradation of lincomycin both in the degradation rate and the degree of decomposition. In addition, the intermediate, H2 O2, plays an important role in the photocatalytic process.